The Reality of the Management of the Corona Pandemic Crisis (Covid 19) in Libyan Universities - Bashier, Assakta Khalil (Journal of Risk and Crisis Management, 2022)
This study aimed at highlight the reality of managing the Corona pandemic crisis (Covid 19) in Libyan public (governmental) universities. To achieve the goal of the research, the descriptive analytical method was used, and the observation was used as a tool for collecting data and information. The study reached a number of results including, the reality of the role- played by public universities in managing the crisis of the Corona pandemic (Covid 19) was not at the desired level, and the lack of sufficient awareness of the importance of the crisis management unit in university administrations. In addition to the absence of a well- studied and effective strategy to protect teaching and learning opportunities in light of the Corona (Covid 19) crisis, which resulted in the inability of most Libyan public universities to switch to distance learning. The study made several recommendations including, the need to establish a specialized unit for crisis management within the administrative structure of Libyan public universities, and the need to develop new strategies in distance education to ensure the continuity of education in times of crisis.